2019
DOI: 10.3390/molecules24061134
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide-Based HIV-1 Fusion Inhibitor with Two Tail-Anchors and Palmitic Acid Exhibits Substantially Improved In Vitro and Ex Vivo Anti-HIV-1 Activity and Prolonged In Vivo Half-Life

Abstract: Enfuvirtide (T20) is the first U.S. FDA-approved HIV fusion inhibitor-based anti-HIV drug. Its clinical application is limited because of its low potency and short half-life. We previously reported that peptide HP23-E6-IDL, containing both N- and C-terminal anchor-tails, exhibited stronger potency and a better resistance profile than T20. Here we designed an analogous peptide, YIK, by introducing a mutation, T639I, and then a lipopeptide, YIK-C16, by adding palmitic acid (C16) at the C-terminus of YIK. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Plasma samples were collected by centrifugation of the whole-blood samples (4500 g/min for 10 min at 4 °C) and were tested for ex vivo anti-HIV-1 activity as previously described [18]. The highest dilution-fold of the plasma sample causing 50% inhibition of HIV-1 infection was calculated, based on which the concentration of an active peptide in plasma was estimated [20] and its half-life and other pharmacokinetic parameters were calculated using MODFIT software [21].…”
Section: Methodsmentioning
confidence: 99%
“…Plasma samples were collected by centrifugation of the whole-blood samples (4500 g/min for 10 min at 4 °C) and were tested for ex vivo anti-HIV-1 activity as previously described [18]. The highest dilution-fold of the plasma sample causing 50% inhibition of HIV-1 infection was calculated, based on which the concentration of an active peptide in plasma was estimated [20] and its half-life and other pharmacokinetic parameters were calculated using MODFIT software [21].…”
Section: Methodsmentioning
confidence: 99%
“…Viral entry inhibitors have been proven effective and safe for the treatment of viral infections (Jiang et al, 1993; Dando and Perry, 2003; Lu et al, 2016; Li et al, 2017; Su et al, 2019). We have previously reported that an HPV entry inhibitor, 3HP-β-LG, is highly effective in blocking the entry of HPV, both high- and low-risk types, into the host cell (Lu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, peptide half-life was increased from 0.4249 to 6.967 h in rats (Feng et al 2018 ). Similarly, attachment of a palmitic acid (C16) chain to C-terminus of an anti-human immunodeficiency virus-1 (HIV-1) peptide YIK (EMTWEEWEKKIEEYIKKIEEILKKSQNQQLDL) extended its serum half-life from 1.3 to 5.9 h in mice (Su et al 2019 ).…”
Section: Npaas Incorporation For Improving Peptide Stability and Relamentioning
confidence: 99%
“…Similarly, conjugation of a C16 chain to the anti-HIV-1 peptide YIK, mentioned above, resulted in twofold improved potency. It was suggested that improved potency was due to enhanced binding of the peptides to the membrane of both host cells and viruses (Su et al 2019 ). It is important to mention that an amphiphilic peptide may contain either a C- or N-terminal alkyl tail and the biological activity can be dramatically affected by the position of the alkylation.…”
Section: Npaas Incorporation For Increasing Peptide Potencymentioning
confidence: 99%